Evaluation of short-duration cassava (Manihot esculenta ) cropping system for proﬁtability, energy eﬃciency and soil restoration - G Suja; J Sreekumar; S Sunitha; Jacob John (Current Horticulture, 2025)
A two-year ﬁeld experiment was conducted at ICAR-CTCRI, Thiruvananthapuram, Kerala, India, to assess the possibility of nutrient saving and develop viable short-duration cassava cropping system during 2013-15. Rice (Oryza sativa L.) var. Aiswarya was sown during the ﬁrst season, followed by greengram [Vigna radiata (L.) R. Wilczek.] (var. Co-Gg-7), blackgram [Vigna mungo (L.) Hepper] (var. Co-6) and soybean (Glycine max (L.) Merr.) (var. JS-95-60). Thereafter, short-duration cassava was planted in split plot design with two varieties, Sree Vijaya and Vellayani Hraswa, in main plots and combination of three preceding pulses and two fertility levels to cassava (full farmyard manure (FYM), N and K (FYM @ 12.5 t/ha, NPK @ 100:0:100 kg/ha); half FYM and N, full K (FYM @ 6.25 t/ ha, NPK @ 50:0:100 kg/ha) in subplots. Rice-pulse-short-duration cassava was productive, proﬁtable, energy eﬃcient and nutrient saving. Both varieties were suitable for crop intensiﬁcation. During ﬁrst year, pulse crops were equally compatible. In subsequent year, greengram proved superior. By the second year, pH, organic C, available N, P and K were not signiﬁcantly aﬀected, but available N, P and K status was higher under pulses. The tuber yield of cassava (30.82 t/ha), tuber equivalent yield (47.39 t/ ha), production eﬃciency (131.63 kg/ha/day), energy equivalent (234.07 x 103 MJ/ha) and proﬁt (additional proﬁt of ₹ 95,758/ha over sole cassava) were higher for rice (var. Aiswarya)-blackgram (var. Co-6)-short-duration cassava (var. Sree Vijaya) system at the reduced fertility level, resulting in a saving of half FYM and, N and full P.